Efforts of Counterfeiting Criminal Acts Passport Identity - Mulyana, Yusep (Universitas Malikussaleh, 2020)
Efforts Made to Overcome Counterfeiting Crimes in the Passport Making System is the Imposition of criminal sanctions related to immigration criminal acts can be carried out effectively if the government conducts effective supervision and legal action against individuals, corporations and officials of relevant government agencies involved in activities that lead to the criminal act of immigration by imposing the maximum sanctions both imprisonment and fines, another effort is by the application of biometric technology, different from the previous technology that separates the making of photographs and fingerprints.Biometric technology can narrow the process within minutes connected online with the central office as a storage of biometric data (face and fingerprint) and between immigration offices to prevent the acquisition of multiple passports to the same person because they have multiple identity documents, the passport data is not necessary again sent to Kemkumham, because the data has been centralized online.